PEMBERIAN GANTI KERUGIAN PEMBANGUNAN JALAN TOL DI KABUPATEN OGAN ILIR - Azarine Nuratna Shafa; Endang Pandamdari (Faculty of Law, Universitas Trisakti, 2023)
In order to implement the supply of fair and appropriate compensation during land acquisition for the public benefit, the implementation of compensation must be founded on land acquisition principles. The question being addressed is whether or not the compensation being granted for the construction of Phase I of the Simpang Indralaya-Muara Enim Toll Road in Ogan Ilir Regency is appropriate or not in light of the principles of land acquisition, as well as whether the provisions of the cassation decision No. 701 K/Pdt/2021 regarding the compensation being granted are appropriate or not in light of those principles. Normative legal research is the research method used to address the issues in the study, and analytical descriptive, secondary data kinds are the research's nature and making judgments based on deductive reasoning. The study's findings demonstrate that the provision of compensation for the Phase I Simpang Indralaya-Muara Enim Toll Road in Ogan Ilir Regency is not in accordance with the principles of agreement and openness, and the contents of the appeal decision number 701 K/Pdt/2021 regarding the provision of compensation strengthen the decision of the Kayuagung district court number 39/Pdt.G/2020/PN Kag which is not in accordance with the principles of agreement on land acquisition.